Genetic polymorphisms of tumour necrosis factor alpha (TNF‐α) promoter gene and response to TNF‐α inhibitors in Spanish patients with inflammatory bowel disease. (17th April 2013) - López‐Hernández, R.; Valdés, M.; Campillo, J. A.; Martínez‐Garcia, P.; Salama, H.; Salgado, G.; Boix, F.; Moya‐Quiles, M. R.; Minguela, A.; Sánchez‐Torres, A.; Miras, M.; Garcia, A.; et al.
Summary Tumour necrosis factor alpha (TNF‐α) has an important role in inflammatory response. Alterations in the regulation of TNF‐α have been implicated in a variety of inflammatory disorders, including Inflammatory bowel disease (IBD). Indeed, a common treatment for IBD is the use of TNF‐α inhibitors. Polymorphisms in the TNF‐α promoter region are known to affect the level of gene expression. Our aim was to investigate the influence of these single nucleotide polymorphisms (SNPs) in TNF‐α promoter gene play in the risk of IBD in a Spanish population and their individual response to anti‐TNF‐α treatment. DNA samples from patients with IBD and controls were screened for TNF‐α −238G/A (rs361525) and −308G/A (rs1800629) SNPs by PCR‐SSOP using a microbeads luminex assay and compared with response to TNF‐α inhibitors. There were not statistical differences in −238G/A and −308G/A allele and genotype frequencies between patients. However, we found an increased frequency of −308A allele and −308GA genotype in these nonresponders patients to TNF‐α inhibitors with respect to responders patients (Pc < 0.05). This −308GA genotype has been classified as high producer of this cytokine. This fact could actually be interesting to explain the different response of patients with IBD with respect to TNF‐α inhibitors. TNF‐α promoter gene polymorphism does not seem to play a role in IBD susceptibility, but particular TNF‐α genotypes may be involved in the different responses to TNF‐α inhibitor treatment in Spanish patients with IBD.